1996
DOI: 10.1007/bf01969709
|View full text |Cite
|
Sign up to set email alerts
|

Improved metabolic action of a bacterial lysine decarboxylase gene in tobacco hairy root cultures by its fusion to arbcS transit peptide coding sequence

Abstract: The gene of a bacterial lysine decarboxylase (ldc) fused to a rbcS transit peptide coding sequence (tp), and under the control of the CaMV 35S promoter, was expressed in hairy root cultures of Nicotiana tabacum. The fusion of the ldc to the targeting signal sequence improved the performance of the bacterial gene in the plant cells in many respects. Nearly all transgenic hairy root cultures harbouring the 35S-tp-ldc gene contained distinctly higher lysine decarboxylase activity (from 1.5 to 30 pkat LDC per mg p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Our results are in agreement with the enhanced cadaverine and anabasine levels observed after feeding lysine to hairy roots of N. tabacum expressing a bacterial LDC gene (Fecker et al 1993). It has been shown that the accumulation of cadaverine and anabasine could be further enhanced by expressing bacterial LDC fused to a chloroplast signal peptides in plant cells (Herminghaus 1996). Although the La-L/ ODC used in this study was targeted to chloroplasts, the La-L/ODC-expressing line produced only 2 times higher anabasine compared to the control line (Figure 2) (Bunsupa, et al 2012a).…”
Section: Discussionsupporting
confidence: 90%
“…Our results are in agreement with the enhanced cadaverine and anabasine levels observed after feeding lysine to hairy roots of N. tabacum expressing a bacterial LDC gene (Fecker et al 1993). It has been shown that the accumulation of cadaverine and anabasine could be further enhanced by expressing bacterial LDC fused to a chloroplast signal peptides in plant cells (Herminghaus 1996). Although the La-L/ ODC used in this study was targeted to chloroplasts, the La-L/ODC-expressing line produced only 2 times higher anabasine compared to the control line (Figure 2) (Bunsupa, et al 2012a).…”
Section: Discussionsupporting
confidence: 90%
“…This localization of La-L/ODC is in agreement with the localization of ODC in chloroplasts (at least partial) (Andreadakis and Kotzabasis, 1996;Tassoni et al, 2003), supporting a hypothesis that L/ODC evolved from an ancestor ODC (as discussed below). Additionally, it was reported that the metabolic action of bacterial LDC in transgenic plants was improved by its fusion to a chloroplast-targeting signal sequence (Herminghaus et al, 1996).…”
Section: Discussion Physiological Roles Of Ldc In Qa-producing Plantsmentioning
confidence: 99%
“…Tryptophan and the terpenoid precursor geraniol are synthesized in the plastids, tryptophan is then decarboxylated in the cytosol, and the two moieties are condensed in the vacuole (De Luca and St-Pierre, 2000). This compartmentation is particularly important to consider as incorrect targeting of transgenes will leave them without the necessary substrates (Herminghaus et al, 1996).…”
Section: Considerations For Plant Metabolic Engineeringmentioning
confidence: 99%